Identification of a novel pyrrolo[2,3-b]pyridine compound as a potent glycogen synthase kinase 3β inhibitor for treating Alzheimer’s disease - Qing-Qing Xun; Jing Zhang; Lei Feng; Yu-Ying Ma; Ying Li; Xiao-Long Shi (Journal of Enzyme Inhibition and Medicinal Chemistry)
Herein, a novel pyrrolo[2,3-b]pyridine-based glycogen synthase kinase 3β (GSK-3β) inhibitor, S01, was rationally designed and synthesised to target Alzheimer’s disease (AD). S01 inhibited GSK-3β, with an IC50 of 0.35 ± 0.06 nM, and had an acceptable kinase selectivity for 24 structurally similar kinases. Western blotting assays indicated that S01 efficiently increased the expression of p-GSK-3β-Ser9 and decreased p-tau-Ser396 levels in a dose‐dependent manner. In vitro cell experiments, S01 showed low cytotoxicity to SH-SY5Y cells, significantly upregulated the expression of β-catenin and neurogenesis-related biomarkers, and effectively promoted the outgrowth of differentiated neuronal neurites. Moreover, S01 substantially ameliorated dyskinesia in AlCl3-induced zebrafish AD models at a concentration of 0.12 μM, which was more potent than Donepezil (8 μM) under identical conditions. Acute toxicity experiments further confirmed the safety of S01 in vivo. Our findings suggested that S01 is a prospective GSK-3β inhibitor and can be tested as a candidate for treating AD.